Tuberculosis Mimicking Metastatic Colon Cancer: A Case Report and Literature Review - Romero-Moreno, Katherine; Cardenas-Velasquez, Andres Felipe (Iatreia)
Introduction: Tuberculosis (TB) infection is known as a great mimicker. Although its primary site is the lungs, it can affect any organ and present with varied manifestations. Intestinal TB represents approximately 3-5% of extrapulmonary TB and can manifest as any gastrointestinal condition with nonspecific symptoms. This underscores the importance of maintaining a high index of suspicion in endemic regions such as Colombia. The main differential diagnoses include inflammatory bowel diseases, other infectious diseases, and neoplasms. Objectives: To describe, through a clinical case, how tuberculosis can mimic other diseases such as cancer. Methods: We present the case of a patient with progressive abdominal pain, weight loss, and changes in bowel habits. Abdominal computed tomography revealed ileocecal thickening and pulmonary images suggestive of infectious versus metastatic involvement, leading to suspicion of advanced colonic neoplasia. Biopsies of the lung, pleura, and ileum yielded positive results for Mycobacterium tuberculosis and ruled out malignancy. Anti-tuberculosis therapy was initiated with good initial response; however, the patient died two months later due to respiratory complications. Conclusions: In countries with high TB prevalence, it should always be considered as a differential diagnosis in the presence of nonspecific gastrointestinal manifestations or when other studies are inconclusive.